The influence of preceding dive cycles on the foraging decisions of Antarctic fur seals - Iwata, T. (Biol Lett, 2015)
The foraging strategy of many animals is thought to be determined by their past experiences. However, few empirical studies have investigated whether this is true in diving animals. We recorded three-dimensional movements and mouth-opening events from three Antarctic fur seals during their foraging trips to examine how they adapt their behaviour based on past experience—continuing to search for prey in the same area or moving to search in a different place. Each dive cycle was divided into a transit phase and a feeding phase. The linear horizontal distance travelled after feeding phases in each dive was affected by the mouth-opening rate during the previous 244 s, which typically covered two to three dive cycles. The linear distance travelled tended to be shorter when the mouth-opening rate in the previous 244 s was higher, i.e. seals tended to stay in the same areas with high prey-encounter rates. These results indicate that Antarctic fur seals follow decision-making strategies based on the past foraging experience over time periods longer than the immediately preceding dive.